2014
DOI: 10.3109/02713683.2014.888450
|View full text |Cite
|
Sign up to set email alerts
|

Learning Effect and Repeatability of Automated Kinetic Perimetry in Healthy Participants

Abstract: The results of the first measurement in the inexperienced participants require careful evaluation, especially for III4e and I4e measured in the peripheral areas. However, because III4e and I4e both showed good repeatability in inexperienced and experienced participants, automated kinetic perimetry may be suitable for measuring the peripheral area using higher stimulus intensities such as III4e and I4e.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 31 publications
1
8
1
Order By: Relevance
“…The learning effect on the mean sensitivity by performing standard automated perimetry is well described in the literature in cases of normal and primary open-angle glaucoma [5,6,[16][17][18][19][20]. In our study, there was no significant change in mean sensitivity during the three examinations.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…The learning effect on the mean sensitivity by performing standard automated perimetry is well described in the literature in cases of normal and primary open-angle glaucoma [5,6,[16][17][18][19][20]. In our study, there was no significant change in mean sensitivity during the three examinations.…”
Section: Discussionsupporting
confidence: 62%
“…In contrast to our results, Weinglass et al [4] stated that older participants forgot the positive learning effect of the previous examination over a short period (less than a month). These results could also be attributed to the correlation of the learning effect with factors other than age, as shown in several studies in the literature [16][17][18][19].…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…17,18 The other explanation is the learning effect which is an important issue in many psychophysical tests. Several studies showed that the individual experience influences the results of standard-automated perimetry 19,20 , but the learning effect using microperimetry is not well established. Previously, an improvement of the macular sensitivity in a second examination in healthy subjects was reported and also in AMD patients.…”
Section: Discussionmentioning
confidence: 99%
“…To remove this bias, a few automated kinetic perimeters have been developed[ 5 – 8 ]. Using automated kinetic perimeters, researchers have been able to examine the optimal stimulus velocity[ 9 ], learning effect, and repeatability in normal participants[ 10 ], and to determine the effect of optical defocus on kinetic perimetry findings[ 11 ].…”
Section: Introductionmentioning
confidence: 99%